2014
DOI: 10.1016/j.contraception.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptive methods and risk of HIV acquisition in women: a systematic review of epidemiological evidence

Abstract: Whether use of various types of hormonal contraception (HC) affect risk of HIV acquisition is a critical question for women's health. For this systematic review, we identified 22 studies published by January 15, 2014 which met inclusion criteria; we classified thirteen studies as having severe methodological limitations, and nine studies as "informative but with important limitations". Overall, data do not support an association between use of oral contraceptives and increased risk of HIV acquisition. Uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 70 publications
2
112
0
1
Order By: Relevance
“…The use of injectable hormonal contraceptives in women increased from 4.5% in 1995 to 23% in 2006 to 2010 (28). A number of studies have suggested an increased risk of acquisition of HIV in association with DMPA (29)(30)(31). It is of interest that one of the highest reported rates of HSV-1 genital herpes was detected in participants of the Herpevac trial study, all of which were required to use a highly effective method of birth control that included hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…The use of injectable hormonal contraceptives in women increased from 4.5% in 1995 to 23% in 2006 to 2010 (28). A number of studies have suggested an increased risk of acquisition of HIV in association with DMPA (29)(30)(31). It is of interest that one of the highest reported rates of HSV-1 genital herpes was detected in participants of the Herpevac trial study, all of which were required to use a highly effective method of birth control that included hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In regions of the world where HIV-1 incidence is highest, more women are newly infected per year than men. 5 While social, behavioral, and economic conditions are certainly factors in the increasing incidence of HIV-1 in women, there has been an emphasis on the role of endogenous 6 and exogenous 7 hormones as cofactors in HIV-1 acquisition or infection and disease progression. Observational and prospective longitudinal studies support that pregnancy and lactation, characterized by high serum progesterone (4-pregnene-3,20-dione or P4) and low serum estradiol [1,3,5(10)-estratriene-3,17beta-diol or E2] levels, are also associated with an increased risk of HIV-1 acquisition compared with nonlactating nonpregnant controls.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding biological contributors to HIV risk in women is therefore important for public health. Although still a topic of great debate there is a growing body of evidence that both endogenous and exogenous ovarian hormones, including estradiol and progesterone, are associated with increased HIV acquisition in women (3)(4)(5)(6)(7). Studies of nonhuman primates have shown that SHIV infection occurs more frequently during the progesteronedominant luteal phase of the menstrual cycle (8,9), and recent in vitro explant cultures of human cervical tissue have also shown that HIV infects explants collected during the luteal phase more productively than those collected during the follicular phase (10).…”
mentioning
confidence: 99%